INHERITANCE RIGHTS FOR LI'AN CHILDREN IN THE STUDY OF MATHEMATICS AND ISLAMIC LAW - Mohammad Tohir; Azmil Yusrul Hana; Saiful Saiful; Ahmad Choirul Anam (LP2M Universitas Ibrahimy, 2023)
Mathematics is a complex science that can be used as a complement to other branches of science. Likewise, the science of faraidh discusses the inheritance rights of property (tirkah) to the heirs of owners who have died, as in one of the problems related to the inheritance rights of other children. So this study aims to describe the role of mathematics in the distribution of inheritance rights of a Li'an child based on the analysis of Islamic law. The research method used is a literature study and focused discussion. The subject of this study is Inheritance and Islamic law, while the object is Li'an's children. The results showed that: (1) mathematics has an essential role in solving the distribution of inheritance rights for other children; (2) according to the perspective of Islamic law, the Li'an child is not related to his father because the lian oath was made by both parents, and the child does not have inheritance rights from the father; (3) other children are only related to their mother, and other children get inheritance rights from their mother's side.